Potentially Mobilizable Geogenic As and Sb in an Agricultural Wetland Soil - Asmaa Rouwane (MDPI AG, 2021)
The mobility of arsenic (As) and antimony (Sb) in soils is controlled by several processes (adsorption/desorption, (co)precipitation/dissolution and oxidation/reduction), depending on various environmental factors that are often convoluted and site-dependent. This study investigated: (i) the content and solid-phase distribution of geogenic As and Sb in a vertical soil profile (0–130 cm) of an agricultural wetland subject into alternating oxic and anoxic conditions induced by periodic waterlogging and (ii) identifies the stability of the As and Sb host phases during soil reduction (laboratory incubation) using a sequential extraction procedure (fractions: loosely and strongly adsorbed, carbonates, easily reducible, reducible, oxidable and residual). The field results showed that, in the deeper, permanently water-saturated soil layers (<60 cm), the amounts of As and Sb were relatively low (As: 8 ± 2 µg·g−1 and Sb: 0.9 ± 0.2 µg·g−1) and related to the Fe content. In the periodically flooded upper soil layers (0–40 cm), the amounts of As and Sb were higher compared to the deeper layers (As: 36 ± 3 µg·g−1 and Sb: 1.14 ± 0.05 µg·g−1). The observed enrichment towards the surface was attributed to the higher content of organic matter (for Sb) and metalloids distribution among the easily reducible fraction (for As). The anoxic laboratory incubation of periodically waterlogged soil showed that, during soil reduction, As is largely mobilized from the easily reducible fraction and undergoes partial readsorption. Unlike As, Sb displayed a higher affinity for more stable soil components (e.g., reducible and residual fractions), which highlights its limited mobility in periodically waterlogged soil compared to As. The potentially mobilizable As and Sb estimated as the sum of the acetate-exchangeable, P-exchangeable, easily reducible and H2O2-organic fractions represent up to 83%, 69% and 53% of the total As and up to 53%, 44% and 54% of the total Sb at 0–20-cm, 40–60-cm and 90–110-cm depths, respectively. Thus, unpolluted soils may act as sources of As and Sb to aquatic environments and therefore have negative consequence on the downstream water quality.